2016
DOI: 10.12944/carj.4.1.08
|View full text |Cite
|
Sign up to set email alerts
|

Household Economic Decisions of Corn Farmers at West Timor, Indonesia

Abstract: The study aimed to identify factors that influence household economic decisions of corn farmers related to the allocation of time, production activities, corn consumption and policy simulation which can increase household economic of corn farmer. Research was conducted at Tesbatan and Camplong II Village, West Timor, Indonesia. Data were analysed using a system of simultaneous equations. Parameter estimation used Two Stage Least Square (2SLS) and simulation analysis was used for getting alternative policy. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Non-food expenditure showed no significant influence on the use of urea and SP-36 fertilizer, but it has positive parameter estimator that indicated there was a tendency that households would reduce the use of fertilizer along with the increase of non-food expenditure. The results of this study were similar to Leki et al (2016) that non-food expenditures to have not significant influence over the use of fertilizer for maize in Timor. This was one the subsistence household indicators that always gave high priority on the effort to meet food needs from other interests.…”
Section: Resultssupporting
confidence: 85%
“…Non-food expenditure showed no significant influence on the use of urea and SP-36 fertilizer, but it has positive parameter estimator that indicated there was a tendency that households would reduce the use of fertilizer along with the increase of non-food expenditure. The results of this study were similar to Leki et al (2016) that non-food expenditures to have not significant influence over the use of fertilizer for maize in Timor. This was one the subsistence household indicators that always gave high priority on the effort to meet food needs from other interests.…”
Section: Resultssupporting
confidence: 85%
“…The results of study conducted by Nuhfil and Yonekure found that household consumption expenditure significantly influenced the decision-making of vegetable farmers household. However, the result of study conducted by Leki et al (2016) showed that non-food expenditure to have not significant influence over the use of fertilizer for maize plant.…”
mentioning
confidence: 93%
“…Considering the unfavourable rainfall pattern during 2019/2020 planting season where most Non-MPCH farmers failed to harvest or very low production of maize. By implementing recommended good practices of maize farming, farmers were able to better manage maize farming with less risk of failure and better yield [14] and involved MPHC farmers have enjoy the reasonable yield and outcomes of the program. They have committed to keep adopting introduced recommendation of good practice of maize farming and hopefully it facilitates for expansion of the program and cultivated land [12,15].…”
Section: Transforming Maize Production Orientationmentioning
confidence: 99%